Which of the following shows the correct process of solving −3(0)+4.5

?(1 point)
Responses

−3(0)+4.5=−1⋅3(0)+4.5=−1⋅1+4.5=−1+4.5=3.5
negative 3 superscript 0 baseline plus 4.5 equals negative 1 times 3 superscript 0 baseline plus 4.5 equals negative 1 dot 1 plus 4.5 equals negative 1 plus 4.5 equals 3.5

−30+4.5=(−3)0+4.5=1+4.5=5.5
negative 3 superscript 0 baseline plus 4.5 equals left parenthesis negative 3 right parenthesis superscript 0 baseline plus 4.5 equals 1 plus 4.5 equals 5.5

−30+4.5=−3⋅0+4.5=0+4.5=4.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5

−3(0)+4.5=−3+4.5=1.5

1 answer

To solve the expression \(-3(0) + 4.5\), we first evaluate \(-3(0)\).

Since any number multiplied by \(0\) is \(0\), we have:

\[ -3(0) = 0 \]

Next, we add \(4.5\) to this result:

\[ 0 + 4.5 = 4.5 \]

Thus, the correct approach is:

\[ -3(0) + 4.5 = 0 + 4.5 = 4.5 \]

Based on the answer options you provided, the correct response is:

−30+4.5=−3⋅0+4.5=0+4.5=4.5
(negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5)